Experiences of homeless women on maternity health service utilization and associated challenge in Aksum town, Northern Ethiopia - Hailay Gebreyesus; Abebe Mamo; Mebrahtu Teweldemedhin; Berihu Gidey; Znabu Hdush; Zewdie Birhanu (BMC, 2019)
Abstract Background Homeless women are a highly vulnerable group for risks of pregnancy and childbirth-related complications. They may also face multiple challenges to access and utilize maternity healthcare services. This study was aimed to explore the experience of homeless women on maternity healthcare service utilization and associated challenges in Aksum Town, Northern Ethiopia. Methods An exploratory qualitative study was employed using in-depth interviews among 22 study participants from February to March 2016. Purposive sampling was used to recruit 12 homeless mothers who gave birth when being homeless in the last 12 months and 10 healthcare providers as key informants. Data were captured using audio recorders and field notes and transcribed, translated verbatim and thematic analysis approach was facilitated using ATLAS.ti7 software. Results The finding reveals that homeless women did not use any of the basic maternity health care services, namely antenatal care, skilled birth attendance, and postnatal care. Lack of permanent place and awareness, and fear of stigma and discrimination were some reasons hindering homeless women from using the services. Conclusions Even though maternity health service utilization is the most crucial intervention to reduce maternal and newborn deaths, this finding shows that maternity health service utilization among homeless women was limited. Socio-cultural, socioeconomic and healthcare-related factors contributed to the non-use of these services. Efforts should be made to address the challenges faced by homeless women to utilize maternity health services.